Renal adaptation in pre-obesity patients with hypertension - Bosch, Agnes; Rauh, Manfred; Striepe, Kristina; Schiffer, Mario; Schmieder, Roland; Kannenkeril, Dennis (Journal of Hypertension, 2024)
Background and hypothesis: Obesity aggravates the risk to develop chronic kidney disease in hypertensive patients. Whether pre-obesity already impairs renal function, renal perfusion and intraglomerular hemodynamics in hypertensive patients is unknown. Methods: Renal hemodynamic profiles were measured using steady state input clearance (infusion of para-amino-hippuric acid and inulin) in 36 patients with primary arterial hypertension stage 1-2 without antihypertensive medication. Intraglomerular pressure (IGP) and resistances of the afferent (RA) and efferent (RE) arterioles were calculated. The study population was divided into two groups based on median of waist circumference (WC) (96 cm) (pre-obesity and non-obesity group1) and median of body mass index (BMI) (26.5 kg/m2) (pre-obesity and non-obesity group2), respectively. Results: All patients were males, non-smoking, aged 36 ± 10 years, with an office blood pressure of 145 ± 8.6/89 ± 11.8 mmHg. None of the patients had cardiovascular disease. Patients from the pre-obese group 1 showed lower glomerular filtration rate (GFR), lower renal plasma flow (RPF) and lower IGP compared to the non-obese group1. Renal vascular resistance (RVR) and RA were higher in the pre-obese group1 compared to the non-obese group1. Similar differences in the hemodynamic profile were found for patients in the pre-obesity group2 compared to the non-obesity group2. Conclusion: The renal hemodynamic profile in hypertensive patients with pre-obesity, irrespective whether defined by WC or BMI, was characterized by a reduced GFR and RPF and by an increased RVR preferentially at the preglomerular site. Our results suggest that hypofiltration is the first phase of renal adaptation in pre-obesity hypertension.
CRIS-Team Scopus Importer:2024-09-20
Keywords: body mass index; clearance analysis; pre-obesity; renal hemodynamic; waist circumference